CHANGING PERCEPTIONS ABOUT CHILDREN: CHALLENGES FOR PRIMARY TEACHERS - DOGRA, BHARTI (THE PRIMARY TEACHER, 2012)
Development of the child is not only a precondition but also a product of education. Recently, human development has taken a turn towards a more “first-person” point of view, i.e. how the world appears to children themselves, a view that allows us to accept that children are not ‘blank slates’ or ‘empty vessels’ and they too have an understanding of their physical, biological as well as social worlds. Older terminologies related to children like “skills”, “abilities”, “potentials” cannot define the actual beliefs, intentions, understandings and misunderstandings of the children. The pedagogy of child learning today is based on the latter. This new approach about children’s knowledge requires not only a new pedagogy but a new perception about the classrooms as well. Classrooms are not places where information is transmitted by an authoritative teacher to children but rather they are places where children collaborate and form communities of learners. Teachers’ role becomes highly challenging in such circumstances. This paper discusses various adjustments required on the part of the primary teachers in the light of changing perceptions about children’s knowledge, learning theories, pedagogy, designing activities and catering to individual differences.